O vento no seu rosto traz histórias para contar: o acolhimento e a alteridade na privação de liberdade de mulheres encarceradas - Tonatto, Regiane Cristina (2021)
This thesis discusses the reception with Otherness in the view of those who decided to welcome the Face of the Other. It is the result of a qualitative research with a phenomenological approach, about the meanings given by the mediators to the reception experienced in the Circles in Movement at the Women's Penitentiary of Foz do Iguaçu-PR, in the year 2019. This action was developed through an extension project entitled “The wind in your face brings stories to tell: life stories of women living in the prison system”, in which interest focused on open dialogue with incarcerated women and on sharing their life trajectories. The idea of exploring the experience lived in prison, in the sense of apprehending the phenomenon of reception, was born with the objective of answering the following questions: how is the person who proposes to welcome affected by the presence and reality of the incarcerated woman? Otherness, in the perspective of Emmanuel Levinas, needs which elements to lead to the renunciation of the Self and to arouse ethical action in welcoming the deprivation of liberty as a form of justice (love)? Both the concept of reception and otherness, present in this thesis, come from studies on the Philosophy of Alterity, by Emmanuel Levinas (2007, 2009, 2010, 2011, 2014 and 2015), the Lithuanian-French philosopher who survived the Holocaust and proposed a radical change in the relationship with the Other. Through the narratives provided by the interviewees, the possibilities of belonging, awareness, justice and non-violence present in the experience of Circles in Movement were evidenced, looking at its application as a way of practicing inclusion, autonomy and the liberation of forgotten subjects by the system, without mastery of exteriority, assimilation/annihilation of difference and imprisonment of the Self within itself. In the end, we were able to conclude that the elements that allow the recognition of the Other and the difference in the deprivation of freedom of women imprisoned by the person who shelters were: the metaphysical desire for the Other; vulnerability before the Face; the language of the face-to-face encounter; the vision of reception as a commitment, teaching and justice; the importance of an emancipating, liberating and fair dialogue; the need for critical and conscious reflection on action and openness to transcendence.